Structures and distributions of SARS-CoV-2 spike proteins on intact virions - Ke, Zunlong; Oton, Joaquin; Qu, Kun; Cortese, Mirko; Zila, Vojtech; McKeane, Lesley; Nakane, Takanori; Zivanov, Jasenko; Neufeldt, Christopher J.; Cerikan, Berati; Lu, John M.; Peukes, Julia; et al. (Nature (London), 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virions are surrounded by a lipid bilayer from which spike (S) protein trimers protrude 1 . Heavily glycosylated S trimers bind to the angiotensin-converting enzyme 2 receptor and mediate entry of virions into target cells 2 – 6 . S exhibits extensive conformational flexibility: it modulates exposure of its receptor-binding site and subsequently undergoes complete structural rearrangement to drive fusion of viral and cellular membranes 2 , 7 , 8 . The structures and conformations of soluble, overexpressed, purified S proteins have been studied in detail using cryo-electron microscopy 2 , 7 , 9 – 12 , but the structure and distribution of S on the virion surface remain unknown. Here we applied cryo-electron microscopy and tomography to image intact SARS-CoV-2 virions and determine the high-resolution structure, conformational flexibility and distribution of S trimers in situ on the virion surface. These results reveal the conformations of S on the virion, and provide a basis from which to understand interactions between S and neutralizing antibodies during infection or vaccination. Cryo-electron microscopy and tomography studies reveal the structures, conformations and distributions of spike protein trimers on intact severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virions and provide a basis for understanding the interactions of the spike protein with neutralizing antibodies.